Impact Test Analysis on Steel Metal Materials and Aluminum - Sunarno Sunarno; Zainuddin Zainuddin (Journal of Social Research, 2023)
Impact testing is carried out to determine the strength of the material against shock resistance, such as brittleness caused by heat treatment or the brittleness of the casting product and the effect of the shape of the product. This test is carried out on a testing machine designed by having a pendulum with a certain weight that swings from a height to provide shock loads, in this test there are two kinds of testing methods, namely the "Izod" method and the "Charpy" method which differ according to the direction of loading on the test material and the position of the test material. This study aims to determine the ductility of ST 37 steel and aluminum from smelting beverage cans combined with oil. The research method used in this research is a direct review in the field then conducting data collection and literature studies including taking report sources from various books, both in campus libraries and libraries outside the campus. The results showed that 1) The impact price on aluminum material was obtained 0.057 Joules / mm2 with the energy given at 4,588 Joules. 2) The impact price on ST37 steel material is 0.192 Joules/mm2 with Energy given at 15.34 Joules.